Uremic Pruritus: From Diagnosis to Treatment - An-Yu Cheng; Lai-San Wong (Diagnostics, 2022)
Uremic pruritus, or chronic kidney disease-associated pruritus, is common, bothersome, and sometimes debilitating in patients with chronic kidney disease or end-stage renal disease. Due to its variable clinical manifestations, the diagnosis of uremic pruritus requires exquisite evaluation. Excluding itch resulting from other dermatological causes as well as other systemic conditions is essential for a proper diagnosis. The pathophysiology of uremic pruritus remains uncertain. Hypotheses including toxin deposition, immune system dysregulation, peripheral neuropathy, and opioid imbalance are supposed. This review summarizes the way to accurately diagnose uremic pruritus and describes the latest treatment options.